FEATURES OF GENERAL ECONOMIC BREAKS OF MODERN DOMESTIC PROPERTY - Biliavska , A.Yu. (The actual problems of regional economy development, 2017)
The article is aimed at studying the general economic preconditions of internal state borrowings and aspects of economic post-crisis development of the country. For the country, it is important to critically examine both its own and foreign experience in enhancing the effectiveness of the post-crisis development of the national economy, with due consideration for the peculiarities of such development for Ukraine in the current conditions in the global economic environment.